Contact problem of conducting and heated punch on a multifield foundation - Rogowski, Bogdan (Zielona Góra: Uniwersytet Zielonogórski)
The solution for a multifield material subjected to temperature loading in a circular region is presented in an explicit analytical form. The study concerns the steady - state thermal loading infinite region (heated embedded inclusion), half - space region and two - constituent magneto - electro - thermo - elastic material region. The new mono - harmonic potential functions, obtained by the author, are used in the analysis of punch problem. The more interested case in which the contact region is annular is analyzed.
Keywords: magneto - electro - thermo - elastic medium; conducting and heated punch; contact problem; exact solution